A utilização do transfer pricing na formação de preços de serviços e procedimentos médico-hospitalares - Yanase, João (2010)
Due to its complexity, hospital organizations need costs control tools that offer important information for decision-making. The use of the Transfer Pricing in the medical services and procedure prices formation is one of those important tools, because it avoids eventual ineffectiveness from being incorporated to the final cost of those products or services. The transfer price differently of the traditional composition of costs, requires from the internal supplier hight competitiveness, otherwise the internal Client has the option to appeal to the market to search better prices and conditions of products or services. The method utilized is the bibliographical and documental research, with preposition of the example, about dates obtained of the hospital, clinical and official sites. The conclusion of this research is that the Transfer Price is perfectly viable on hospital organizations wich are structurally decentralized. For the success in the utilization of this tool at heathy management, is indispensable the commitment of all collaborators, from the ground up